Three Phase Power Supply for Induction Motor and Power Factor Correction Trainer - Loh Bojeng, Abdul Hafiz; Norjali, Rasida; Mohamad Syah Rizal Abdullah (Progress in Engineering Application and Technology, 2024)
Three phase power supply is commonly used in high total load demand because the ability to supply ever-higher power densities is particularly important as data centers and server rooms continue to experience ever-higher densities. This project aims are to provide the three-phase power supply at Makmal Peralatan dan Pengujian at UTHM Pagoh and adding on some safety future and to improve hands on experiences for students in laboratory. This Three-Phase Power Supply Optimization Project aims to enhance the efficiency, stability, and reliability of three-phase power distribution systems. The objective of the Three-Phase Power Supply Project is to produce 230V for single phase and 415V for three phases and to evaluate the performance of three-phase power distribution systems’ stability, dependability, and efficiency. Industrial and commercial electrical networks require three-phase power because it offers a more stable and balanced power supply than single-phase systems. The main goal of this project is to give facility to this laboratory with some safety future which can remotely trip and real time monitoring for three-phase power systems. As its name implies, 3-phase power systems provide three separate currents, each separated by one-third of the time it takes to complete a full cycle. But, as opposed to single-phase, where the two hot legs are always 180 degrees apart, with 3-phase, the currents are separated by 120 degrees.